Intersectionality Narratives in the Classroom "Outsider Teachers" and Teaching Others - Makris, Sara (Springer International Publishing, 2018)
This book portrays the experiences of self-described "outsider" or "other" teachers-teachers whose identities set them apart from their students based upon combinations of race, class, gender identity, sexual orientation, nationality, ability status, religion, or other identity characteristics. The teachers profiled bring experiences of social isolation and difference into the classroom and demonstrate perspectives and habits of mind that inform a nuanced approach to interaction with students.